The Mechanism of Selecting Priority Investment Facilities on the Basis of Integral Indicators of Competitiveness - Natalia E. DERKACH; Olga I. SOLODUKHINA; Svetlana A. STARYKH; Daniel I. RASPOPIN (Communications of International Proceedings, 2020)
The paper proposes an algorithm for selecting priority investment facilities on the basis of a competitiveness assessment technique through the effects of investees on micro-, mini -, meso - and macro-levels.  Levels of competitiveness are considered. Theoretical formulas for the measurement of competitiveness are proposed.
Keywords: Competition; competitiveness; competitiveness assessment techniques.